The Higher Education Enrollment Decision: Feedback on Expected Study Success and Updating Behavior. Issue 1 (2nd January 2019) - van Klaveren, Chris; Kooiman, Karen; Cornelisz, Ilja; Meeter, Martijn
Abstract: This study examines whether providing students with information on their future study success will influence their higher education enrollment decision and lower first-year dropout as a consequence. A randomized field experiment is conducted among 313 law and social science applicants at the Vrije Universiteit Amsterdam. The main results suggest that (a) students are generally overly positive about their future performance, (b) enrollment rates increase by 25% if students receive information on future study success, but (c) providing information to students does not reduce first-year dropout. An important conclusion is that the higher enrollment decision is not driven by the extent to which students are self-serving biased or by their updating behavior. Instead this decision seems to be influenced by a fear of failure, in the sense that students who receive a pass-signal (fail-signal) with respect to future study success enroll with higher (lower) probability.